Granulocyte‐macrophage colony‐stimulating factor initiates amniotic membrane rupture and preterm birth in a mouse model. (6th April 2021) - Nold, Christopher; Esteves, Kristyn; Jensen, Todd; Vella, Anthony T.
Abstract: Objective: Preterm premature rupture of membranes is associated with 30% of all preterm births. The weakening of amniotic membranes is associated with an increase in matrix metallopeptidases (MMPs) along with a decrease in their inhibitors, tissue inhibitor metallopeptidases (TIMPs). Additionally, granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) has been shown to weaken fetal membranes in‐vitro. We hypothesize pregnant mice treated with GM‐CSF lead to increased MMPs:TIMPs resulting in membrane rupture and preterm birth. Study Design: Pregnant CD‐1 mice on gestational day 17 received either an intrauterine injection of GM‐CSF or vehicle control. A second series of mice were administered an intrauterine injection of Lipopolysaccharide along with either anti‐mouse GM‐CSF or control antibody. Mice were evaluated for rupture of membranes and/or preterm birth and the uterus, amniotic fluid, and serum were collected for analysis. Results: 87.5% of GM‐CSF mice exhibited evidence of membrane rupture or preterm birth, compared with 0% in control mice ( p  < .001). Treatment with GM‐CSF decreased the expression of TNFα ( p  < .05) while increasing the ratio of MMP2:TIMP1 ( p  < .05), MMP2:TIMP2 ( p  < .05), MMP2:TIMP3 ( p  < .001), MMP9:TIMP1 ( p  < .01), MMP9:TIMP2 ( p  < .05), MMP9:TIMP3 ( p  < .001), and MMP10:TIMP1 ( p  < .05). Mice treated with LPS and the GM‐CSF antibody resulted in a decrease in the ratio of MMP2:TIMP1 ( p  < .0001) compared with controls. Conclusion: These studies demonstrate GM‐CSF will result in membrane rupture and preterm birth by increasing the ratio MMPs:TIMPs in our animal model. By increasing our understanding of the molecular pathways associated with GM‐CSF, we may be able to develop future therapies to prevent preterm birth and reduce neonatal morbidity.